Neoadjuvant Chemotherapy Alters Neuropilin-1, PlGF, and SNAI1 Expression Levels and Predicts Breast Cancer Patients Response - Al-Zeheimi, Noura; Naik, Adviti; Bakheit, Charles Saki; Al Riyami, Marwa; Al Ajarrah, Adil; Al Badi, Suaad; Al Baimani, Khalid; Malik, Kamran; Al Habsi, Zamzam; Al Moundhri, Mansour S.; Adham, Sirin A. (Frontiers in Oncology, 2019)
Circulating proteins hold a potential benefit as biomarkers for precision medicine. Previously, we showed that systemic levels of neuropilin-1 (NRP-1) and its associated molecules correlated with poor-prognosis breast cancer. To further identify the role of NRP-1 and its interacting molecules in correspondence with patients' response to neoadjuvant chemotherapy (NAC), we conducted a comparative study on blood and tissue samples collected from a cohort of locally advanced breast cancer patients, before and after neoadjuvant chemotherapy (NAC). From a panel of tested proteins and genes, we found that the levels of plasma NRP-1, placenta growth factor (PlGF) and immune cell expression of the transcription factor SNAI1 before and after NAC were significantly different. Paired t-test analysis of 22 locally advanced breast cancer patients showed that plasma NRP-1 levels were increased significantly (p = 0.018) post-NAC in patients with pathological partial response (pPR). Kaplan–Meier analysis indicated that patients who received NAC cycles and their excised tumors remained with high levels of NRP-1 had a lower overall survival compared with patients whose tissue NRP-1 decreased post-NAC (log-rank p = 0.049). In vitro validation of the former result showed an increase in the secreted and cellular NRP-1 levels in resistant MDA-MB-231 cells to the most common NAC regimen Adriyamicin/cyclophosphamide+Paclitaxel (AC+PAC). In addition, NRP-1 knockdown in MDA-MB-231 cells sensitized the cells to AC and more profoundly to PAC treatment and the cells sensitivity was proportional to the expressed levels of NRP-1. Unlike NRP-1, circulating PlGF was significantly increased (p = 0.014) in patients with a pathological complete response (pCR). SNAI1 expression in immune cells showed a significant increase (p = 0.018) in patients with pCR, consistent with its posited protective role. We conclude that increased plasma and tissue NRP-1 post-NAC correlate with pPR and shorter overall survival, respectively. These observations support the need to consider anti-NRP-1 as a potential targeted therapy for breast cancer patients who are identified with high NRP-1 levels. Meanwhile, the increase in both PlGF and SNAI1 in pCR patients potentially suggests their antitumorigenic role in breast cancer that paves the way for further mechanistic investigation to validate their role as potential predictive markers for pCR in breast cancer.